(untitled) (SAARC Journal of Agriculture, 2015)
Population parameters of Notopterus notopterus (Pallas, 1769) from length-frequency data collected from Kaptai Reservoir of Rangamati, Bangladesh from January, 2013 to December, 2013 were calculated by using FiSAT software. The asymptotic total length (L?) and growth coefficient (K) were estimated to be 34.91cm and 0.38 y?1respectively. The instantaneous rate of natural mortality (M), fishing mortality (F) and total mortality (Z) were estimated to be as 0.91 y?1, 0.28 y?1and 1.19 y?1 respectively. The value of exploitation rate (E) was found to be 0.24 which clearly pointed toward moderate or less fishing pressure (E<0.50) of N. notopterus in the Kaptai reservoir of Bangladesh. The recruitment of the species was found throughout the year with two peaks - one from March-April; and another from May- June. Virtual population analysis (VPA) estimated that the maximum numbers of N. notopterus were caught between 10.50 cm to 32.50 cm with maximum F value (0.80 y?1) in the mid length of 18.30 cm. During the year 2013 the total catch of N. notopterus was found to be 664.5 MT, which contributed about 7.78% of the total catch of Kaptai Lake. Relative yield per recruit (Y/R) and biomass per recruit (B/R) suggested that the natural mortality should be reduced to 0.91 y?1 by proper management to obtain a maximum sustainable exploitation rate (Emax= 0.828) for the species in the reservoir. DOI: http://dx.doi.org/10.3329/sja.v12i2.21923 SAARC J. Agri., 12(2): 112-122 (2014